2013
DOI: 10.1155/2013/613596
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Integrative Therapies in Patients with Amyotrophic Lateral Sclerosis in Shanghai, China

Abstract: Objective. To investigate the current use of integrative therapies (IT) in the treatment of patients with amyotrophic lateral sclerosis (ALS). Methods. A cross-sectional, multicenter clinical epidemiological survey was conducted in 12 hospitals in Shanghai. We investigated the type and frequency of IT use and determined whether the use of IT correlated with demographic, social, or disease-specific characteristics in our patient population. Results. A total of 231 (89.5%) of 258 patients with ALS were eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 12 publications
1
50
0
Order By: Relevance
“…Only two out of the seven papers included in this review reported a prevalence rate of CAM use among ALS patients [18,19]. A cross-sectional study in Germany published in 2001 reported a CAM use rate of 54% among 171 ALS patients who were members of the German Association for Neuromuscular Disease [18].…”
Section: Prevalence Of Cam Use In Alsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only two out of the seven papers included in this review reported a prevalence rate of CAM use among ALS patients [18,19]. A cross-sectional study in Germany published in 2001 reported a CAM use rate of 54% among 171 ALS patients who were members of the German Association for Neuromuscular Disease [18].…”
Section: Prevalence Of Cam Use In Alsmentioning
confidence: 99%
“…A cross-sectional study in Germany published in 2001 reported a CAM use rate of 54% among 171 ALS patients who were members of the German Association for Neuromuscular Disease [18]. Another cross-sectional study conducted in 2012-2013 in ALS patients from 12 hospitals in one Chinese city found that 99% of the respondents (n = 229) had used at least one CAM [19].…”
Section: Prevalence Of Cam Use In Alsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both frequent nighttime urination (FNU) and sialorrhea are explained by the theory of traditional Chinese medicine (TCM) in terms of dysfunction of body fluid control. TCM theory considers these symptoms to be a Qi deficiency in the spleen and kidney [4]. We used the TCM herbs of Jian-Pi Lian-Se Tang (JPLST) which can improve the Qi function of the body and showed that JPLST improved astringency function after 6 weeks of treatment in patients who suffered from salivation and FNU compared to patients not treated with TCM.…”
Section: Introductionmentioning
confidence: 99%